Palynology, sedimentary ancient DNA, biomarkers, macrocharcoal and sedimentological data from Lake Otjikoto, Namibia - Ximena Tabares; Heike Hildegard Zimmermann; Elisabeth Dietze; Gregor Ratzmann; Lukas Belz; Andrea Vieth-Hillebrand; Lydie M Dupont; Heinz Wilkes; Benjamin Mapani; Ulrike Herzschuh (PANGAEA, 2019)
We present a multi-proxy record (fossil pollen, sedimentary ancient DNA, biomarkers, compound-specific carbon (δ13C) and deuterium (δD) isotopes, bulk carbon isotopes (δ13Corg), grain size, geochemical properties) from Lake Otjikoto, Namibia. Samples were extracted from sediment cores 15OJ10 and 15OJ06. These data document the compositional and environmental changes associated with shrub encroachment in semi-arid savanna environments.
Supplement to: Tabares, X et al. (2019): Vegetation state changes in the course of shrub encroachment in an African savanna since about 1850 CE and their potential drivers. Ecology and Evolution, https://doi.org/10.1002/ece3.5955